Promosi Kesehatan dan Pencegahan Anemia Melalui Video Animasi dan Pemberian Suplementasi Besi pada Remaja Putri - Yussie Ater Merry; Lita Angelina Saputri; Faridah Bd (CV. CENDIKIA JENIUS INDONESIA, 2025)
Anemia in adolescence is a condition in which hemoglobin levels are less than 12 g%. Anemia causes hemoglobin can’t be enough to bind and carry oxygen from the lungs to the the body. Based on the data, young women in Nanggalo District, especially Kurao Pagang Village, have never received information about Anemia Prevention using Animated Videos. The purpose of this community service is to increase the knowledge of adolescent girls about anemia prevention through animated videos so that adolescents can increase their nutritional intake in preparation for becoming mothers-to-be. The location of this activity is in Nanggalo District, Kurao Pagang Village, Padang. The activity is occured from July to November 2024 with 60 people. This activity include presentation about anemia, questions and answers and viewing animated video about anemia. Evaluation is carried out with pretest and posttest. The results obtained were the increase of the average knowledge about anemia by 87.5% and about iron tablets by 74.1%. Conclusion: there was an increase in the knowledge of adolescent girls about anemia prevention after obtaining Health Educationby using animated videos. It is hoped that the next community service will involve more community presence. So it can be carried ou continously.